2005
DOI: 10.1111/j.1742-4658.2005.04752.x
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin‐related peptide precursors in two cockroach species

Abstract: Tachykinins constitute a family of multifunctional neuropeptides whose signaling mechanisms seem to be partially conserved through evolution [1][2][3][4][5]. Although the tachykinin peptides display only limited sequence identities when comparing invertebrates and mammals, their G-protein-coupled receptors (GPCRs) display more striking similarities, suggesting ancestral relationships [4,5]. The three principal mammalian tachykinins, substance P, neurokinin A and neurokinin B, are processed from two precursors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Direct peptide profiling of nervous tissue or single cells in other insects revealed much higher signal intensities (e.g., Ma et al, 2000;Predel et al, 2005Predel et al, , 2006Berg et al, 2006). The low signal intensity appears thus to be an intrinsic property of M. sexta tissue, as also mass spectra obtained by direct profiling of neurohemal organs of M. sexta show lower signal intensities than those obtained from homologous organs of other insects (Predel et al, 2003;Predel, unpublished observations).…”
Section: Discussionmentioning
confidence: 87%
“…Direct peptide profiling of nervous tissue or single cells in other insects revealed much higher signal intensities (e.g., Ma et al, 2000;Predel et al, 2005Predel et al, , 2006Berg et al, 2006). The low signal intensity appears thus to be an intrinsic property of M. sexta tissue, as also mass spectra obtained by direct profiling of neurohemal organs of M. sexta show lower signal intensities than those obtained from homologous organs of other insects (Predel et al, 2003;Predel, unpublished observations).…”
Section: Discussionmentioning
confidence: 87%
“…Surprisingly, we also found that several neuropeptide precursors (Lom-NPF1a, Lom-NPF2, Lom-sNPF, Lom-TK, Lom-OK-B and Lom-NPP1) showed detectable expression levels in locust midgut. OK, TK and ITP are conserved brain-gut peptides, with functions including myotropic effects and regulation of ion and fluid transport (Audsley et al, 2013;Begum et al, 2009;Pascual et al, 2004;Predel et al, 2005). They may act as important factors to regulate peristalsis of digestive tract and food digestion in locust midgut.…”
Section: Discussionmentioning
confidence: 99%
“…In D. melanogaster, more than 60 peptides may exist, and in the cockroach Periplaneta americana, more than 80 have been identified so far (see Predel et al 2005). Many of the peptides encoded on a given precursor display similar amino acid sequences.…”
Section: Neuropeptides Identified In Insectsmentioning
confidence: 96%
“…In several cases, most or all of the predicted peptides are actually cleaved from the precursor. For example, five of the six tachykinin-related peptides (TKRPs) of the D. melanogaster precursor and all those of the cockroaches so far studied have been identified in brain tissue by mass spectrometry (Winther et al 2003;Predel et al 2005). Other precursors have been assayed in a similar fashion (see Baggerman et al 2002Baggerman et al , 2005Predel et al 2004a,b).…”
Section: Neuropeptides Identified In Insectsmentioning
confidence: 97%
See 1 more Smart Citation